Structural integrity of RyR2 clusters controls cardiac calcium leak - Noren, Andrew; Shiferaw, Yohannes (Frontiers in Physiology, 2025)
BackgroundCalcium (Ca) leak from the sarcoplasmic reticulum contributes to cardiac arrhythmias, yet the structural mechanisms regulating spontaneous Ca release from ryanodine receptor type 2 (RyR2) clusters remain poorly understood.MethodsWe developed a computational model in which each RyR2 channel comprises four interacting subunits embedded within spatially organized clusters. This framework captures both cooperative gating within individual channels and coupling between neighboring channels.ResultsOur simulations reveal that spontaneous Ca spark timing depends exponentially on RyR2 cluster structural integrity. This exponential sensitivity means that modest disruptions in cluster structure, such as partial fragmentation, can increase spontaneous Ca spark frequency by 100–1,000 fold.ConclusionsCluster structural integrity provides a powerful control mechanism for Ca leak and represents a promising therapeutic target for restoring Ca homeostasis in cardiac myocytes.